SLA/LP/tRNP(Ser)Sec antigen in autoimmune hepatitis: identification of the native protein in human hepatic cell extract - Volkmann, Martin; Luithle, Daniel; Zentgraf, Hanswalter; Schnölzer, Martina; Fiedler, Sabine; Heid, Hans; Schulze-Bergkamen, Andrea; Strassburg, Christian P.; Gehrke, Sven; Manns, Michael P. (Journal of autoimmunity, 2010)
A diagnostic subgroup of AIH type 1 is characterized by specific serum antibodies against soluble liver protein. The respective autoantigen was named SLA/LP/tRNP(Ser)Sec, after three homologous recombinant polypeptides were isolated from expression gene libraries. We analyzed human cultured liver cells for the human homologue of recombinant SLA/LP/tRNP(Ser)Sec by antigen purification. In addition, a monoclonal antibody was generated against recombinant SLA-p35, a truncated recombinant SLA-reactive polypeptide...
Online veröffentlicht am 14. August 2009
Im Titel erscheint die Zeichenfolge "(Ser)Sec" hochgestellt
Gesehen am 12.09.2023